Circles Are Detected Faster Than Downward-Pointing Triangles in a Speeded Response Task. (October 2020) - Chuquichambi, Erick G.; Rey, Carlos; Llames, Rosana; Escudero, Juan T.; Dorado, Alejandro; Munar, Enric
Simple geometric shapes are associated with facial emotional expressions. According to previous research, a downward-pointing triangle conveys the threatening perception of an angry facial expression, and a circle conveys the pleasant perception of a happy facial expression. Some studies showed that downward-pointing triangles have the advantage to capture attention faster than circles. Other studies proposed that curvature enhances visual detection and guides attention. We tested a downward-pointing triangle and a circle as target stimuli for a speeded response task. The distractors were two stimuli that resulted from the mixture of both targets to control for low-level features' balanced presentation. We used 3 × 3, 4 × 4, and 5 × 5 matrices to test whether these shapes led attention to an efficient response. In Experiment 1, participants responded faster to the circle than to the downward-pointing triangle. They also responded slower to both targets as the number of distractors increased. In Experiment 2, we replicated the main findings of Experiment 1. Overall, the circle was detected faster than the downward-pointing triangle with small matrices, but this difference decreased as the matrix size increased. We suggest that circles capture attention faster because of the influence of low-level features, that is, curvature in this case.